STRUCTURAL STUDY IN THE COLLECTION OF THE SHORT STORIES OF KOMPAS 2014 AND THEIR RELEVANCE AS LITERATURE LEARNING MATERIALS IN HIGH SCHOOL OF THE ACADEMIC YEAR 2021-2022 - Prayogo, Yogi Aryo; Kusyani , Diah; Arianto , Arianto (LUMBUNG AKSARA, 2022)
This study aims to describe: (1) the intrinsic elements of the 2014 Kompas Selected Short Story Collection; (2) The relevance of the 2014 Kompas Selected Short Story Collection as literature learning material in high school. The research approach used in this research is descriptive qualitative using structural methods and content analysis strategies. The data source used is the 2014 Kompas Selected Short Story Collection. The conclusions of this research are: (1) the intrinsic elements contained in the 2014 Kompas Selected Short Story Collection include plot, characterization, setting, theme, message, point of view and language style. These elements differ from one short story to another. (2) A collection of short stories selected by Kompas 2014 and their teaching as a result of the analysis of the intrinsic elements contained in the short stories Kompas 2014 are relevant when used in teaching literature in high school. The results of the research findings with a structural study indicate that there are (1) short stories in the body of Tarra, in the Tree Rahim: (a) socio-cultural themes, (b) canpuran plots, (c) place settings; passiliran, time setting; morning and evening, background atmosphere; tense, (d) Runduma, Lola, Ambe, Indo, (tarra tree), Runduma's grandfather, (e) first person point of view. (2) The striped tiger short story: (a) the theme of forest-life exploitation, (b) mixed plot, (c) the menot character (striped tiger), (d) the setting; hamlet of the Great Prison, time setting; day and night, social setting; community (e) language style; typical of Sumatra, (f) point of view; the third person. (3) Short story The Death of a Demonstrator: (a) the theme of the struggle, (b) the plot backwards, (c) the setting; auditorium, Ratih's house, campus roundabout, in front of campus, rented house, Eka's boarding room, alleys and Munarman street, time setting; morning, afternoon and evening, background atmosphere; joking, sad and tense, (d) characters: Ratih, Eka, and Arman (Munarman), (e) point of view: third person omniscient. (4) The short story Bukit Cahaya: (a) moral theme, (b) forward plot, (c) setting; office, hamlet, bay, small huts, house, time setting; evening, social setting; offices and villages, (b) laur-forward, (c) place settings; bus stops, highways, food stalls, cafes, cars, (d) sales executive youth figures, working women, (e) first person point of view. (6) Short story of Woman and Ants in Her Head: (a) negative thinking theme, (b) forward flow, (c) setting; garden, house, room, time setting; morning and evening, (d) character; woman, her husband, woman (paranoit), (e) third person point of view. The value of character education is found in each short story. The use of the method of studying literary works through the structure is expected to increase students' interest in deepening and appreciating the literary works of Indonesian writers. In addition, this structural study can make literature learning in high school more effective and efficient.